Shear controlled alignment of short carbon fibers in copper matrix composite green samples produced by powder injection molding - ., Irfan Shirazi, Faiz Ahmad, M Rafi Raza, Ali S Muhsan, M Aslam (2015)
The tensile properties of short fiber reinforced composites are enhanced if fiber alignment in the load direction is achieved. Powder injection molding provides partial alignment of fibers in molded parts and shows a skin-core effect. The objective of this study was to align fibers completely in flow direction and reducing skin-core effect in green samples. This objective was achieved by changing the type of flow during molding by changing sprue geometry in a way that diverging flow is developed in it. This diverging flow was converted to converging flow when feedstock entered mold cavity and generated shear to align fibers. This sprue modification was helpful in aligning short fibers in flow direction and eliminating skin-core effect.